Introduction to the Proceedings of the 49th European Marine Biology Symposium. (11th June 2015) - Sukhotin, Alexey; Frost, Matthew; Hummel, Herman
Abstract : In September 2014 a group of 130 marine biologists from 26 countries assembled in the 49th European Marine Biology Symposium (EMBS) held in Saint Petersburg, Russia. The EMBS is a series of annual conferences providing presentations and dialogue in a fairly informal atmosphere – the perfect conditions for encouraging interactions on state-of-art issues in marine science in Europe and beyond. The 49th symposium, organized by the Zoological Institute of the Russian Academy of Sciences, included four keynote lectures, 65 oral presentations and 92 poster contributions under the overarching theme 'A variety of interactions in the marine environment'.